The Pierre Auger Observatory I: The Cosmic Ray Energy Spectrum and Related Measurements - Collaboration, TPA; Abreu, P; Aglietta, M; Ahn, E; Albuquerque, I; Allard, D; Allekotte, I; Allen, J; Allison, P; Castillo, J; Alvarez-Muñiz, J; Ambrosio, M; et al. (2011)
Studies of the cosmic ray energy spectrum at the highest energies with the Pierre Auger Observatory